Performance analysis of tunnel broker through open virtual private network - Rendy Munadi; Danu Dwi Sanjoyo; Doan Perdana; Fidar Adjie (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Tunnel Broker uses automatic configuration tunneling mechanism for IPv6 clients connected to IPv4 internet. Connectivity between clients and service providers in IPv6 is urgently needed. Open VPN as a provider implemented configures it by a VPN network, so IPv6 and IPv4 public IP clients can easily connect to the server. In this research focused on the performance of tunnel broker mechanism by utilizing open VPN as access to the network. IPv6 tunnel broker is developed by installing Open VPN and providing IPv6 IPs. Implementation of public IP usage in observing the performance of tunnel broker development is done in BCN Telkom Laboratory Network. The measurement results show that TCP and UDP throughput of IPv6 is slightly higher than IPv4. The research using OpenVPN as a server Tunnel Broker for client access to the server is still rarely done, especially in the field of the network based on Internet Protocol.